Salvage of Chronic Therapy‐Resistant Bilateral Charcot Foot Osteoarthropathy with Signs of Osteomyelitis. Issue 7 (19th May 2022) - Kidron, Ariel; Nguyen, Hiep H.; Bayer, Jack; Durkin, Michael; Harris, Daniel; Dang, Helen; Diehl, Matt; Silver, Larry
Abstract : Charcot arthropathy is an insidious condition affecting the lower limbs of diabetic patients. It is a complication of diabetic neuropathy resulting from subsequent Wallerian degeneration of the nerves. This complication may eventually lead to limb amputation and a poor patient prognosis if not diagnosed and treated successfully. Herein, we report the case of a 73‐year‐old female who presented with rapidly progressive bilateral Charcot foot over a 5‐week period, necessitating an exostectomy on the mid foot, specifically on the cuboid bone and the navicular cuneiform joint. Her presentation with rapidly progressing foot ulcers on the plantar aspect prompted initial treatment based on osteomyelitis. The report will therefore serve as a useful guide on how to properly treat Charcot foot, which may present in an atypical manner. Abstract : A 73‐year‐old female with a history of Type II Diabetes Mellitus presents with 5 week history of progressing bilateral Charcot foot complicated by osteomyelitis. We describe the patient's rapid progression and the treatment and management of the disease.